INVESTIGATION OF ELECTROCATALYTIC ACTIVITY OF SOME METALLIDES AND INTERMETALLIC COMPOUNDS IN HYDROGEN EVOLUTION REACTION AND DEVELOPMENT OF METHODS OF ITS INCREASE - Shein, A.B.; Kichigin, V.I.; Panteleeva, V.V. (Perm Federal Research Centre Journal, 2017)
Electrocatalytic activity of some metallides and intermetallic compounds in a hydrogen evolution reaction in acidic and alkaline solutions has been investigated. Ways of increasing the activity of the investigated materials in the hydrogen evolution reaction have been elaborated. Diagnostic criteria applicable to the method of electrochemical impedance spectroscopy have been suggested, which allow determining the nature of the reaction steps of the hydrogen evolution reaction, the hydrogen adsorption isotherm type, and establishing the presence or absence of hydrogen absorption, determining the values of the rate constants of the reaction stages of evolution and absorption of hydrogen.